Recensión: Christopher O. Tollefsen, Lying and Christian Ethics - Poblete, José Antonio; Concha Infante, Marcelo (Studium. Filosofía y Teología, 2017)
Christopher O. Tollefsen, Lying and Christian Ethics, New York, Cambridge University Press, 2014, xii + 209 pp., ISBN: 978-1-107-06109-5